XV International Conference on Durability of Building Materials and Components. eBook of Proceedings 2020
DOI: 10.23967/dbmc.2020.204
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Thermal Performance of the Building Envelope - Beyond Common Practice

Abstract: Performance metrics serve as useful tools and indicators for many applications. For the building industry, various metrics exist; typically, these metrics do not assess the whole building performance. Instead, these represent separate components or heat transfer mechanisms of a building like R-value, U-factor/value, and airtightness. The mechanisms defined under these metrics all contribute significantly to the overall thermal performance of a building but will rarely act independently. There are metrics that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The effective U-value is a way of correcting the steady-state measured material properties, reflecting the actual performance of a construction element in dynamic conditions. The study [5] from Newcastle in Australia emphasizes that the steady-state thermal resistance (R-value) is insufficient to describe the energy performance of a construction element alone. It concluded that the thermal mass is a crucial parameter in the overall energy performance of a house and is the reason for the deviation between steady-state measured U-value and effective U-value.…”
Section: Introductionmentioning
confidence: 99%
“…The effective U-value is a way of correcting the steady-state measured material properties, reflecting the actual performance of a construction element in dynamic conditions. The study [5] from Newcastle in Australia emphasizes that the steady-state thermal resistance (R-value) is insufficient to describe the energy performance of a construction element alone. It concluded that the thermal mass is a crucial parameter in the overall energy performance of a house and is the reason for the deviation between steady-state measured U-value and effective U-value.…”
Section: Introductionmentioning
confidence: 99%